A responsabilidade socioeconômica e ambiental no processo de sustentabilidade e desenvolvimento local: estudo de caso das associações de catadores RESOL e AREPI - Oliveira, Elgson Decarle de (2013)
During the past five decades a large number of unemployed people has found in the activity of collecting recyclable waste a way to survive. Despite the low appreciation of the “Catadores” work by society, they have been organizing themselves into cooperatives and associations to obtain better conditions of life and work. In such organizations they have been taking part of several recycling projects together with local administrations. This work identifies and analyzes two associations of “Catadores” of recyclable waste, the Associação dos Recicladores de Pinhais – AREPI and the Associação dos Trabalhadores de Reciclagem de Resíduos de Colombo – RESOL, located in the metropolitan region of Curitiba - PR. The objective is to analyze the administrative management related to the development of the socioeconomic and environmental sustainability of these enterprises. The qualitative research was adopted as the methodology of this study and included semi-structured interviews with the presidents of the associations, questionnaires to all members, two years and a half of observations and notes. The data obtained from the interviews and questionnaires produced information that enabled the analysis of their administrative managements. It was possible to conclude that the enterprises present some similar features characterized by: social inclusion; creation of jobs; environmental preservation due to solid waste recycling; defense of the “Catadores” rights by laws; Forum Lixo e Cidadania and public policies to support the “Catadores”, which has provided an increase in the income of the associated “Catadores” of 131%, since the arrival of new trucks donated by FBB and FUNASA. Moreover, the gender issue is a major factor where 93% of the members are women. This study concluded that the associations need to adopt a business strategic planning to ensure sustainable development in face of the competitive recycling sector. In front of the new scenario established by the National Solid Waste Policy, the strengthening of the infrastructure and the recycling network will contribute to the process of developing the sustainability of the “Catadores” associations.